A search for amino acids and nucleobases in the Martian meteorite Roberts Massif 04262 using liquid chromatography‐mass spectrometry. (15th March 2013) - Callahan, Michael P.; Burton, Aaron S.; Elsila, Jamie E.; Baker, Eleni M.; Smith, Karen E.; Glavin, Daniel P.; Dworkin, Jason P.
Abstract The investigation into whether Mars contains signatures of past or present life is of great interest to science and society. Amino acids and nucleobases are compounds that are essential for all known life on Earth and are excellent target molecules in the search for potential Martian biomarkers or prebiotic chemistry. Martian meteorites represent the only samples from Mars that can be studied directly in the laboratory on Earth. Here, we analyzed the amino acid and nucleobase content of the shergottite Roberts Massif (RBT) 04262 using liquid chromatography‐mass spectrometry. We did not detect any nucleobases above our detection limit in formic acid extracts; however, we did measure a suite of protein and nonprotein amino acids in hot‐water extracts with high relative abundances of β‐alanine and γ‐amino‐n‐butyric acid. The presence of only low (to absent) levels of several proteinogenic amino acids and a lack of nucleobases suggest that this meteorite fragment is fairly uncontaminated with respect to these common biological compounds. The distribution of straight‐chained amine‐terminal n‐ω‐amino acids in RBT 04262 resembled those previously measured in thermally altered carbonaceous meteorites (Burton et al. 2012; Chan et al. 2012). A carbon isotope ratio of −24‰ ± 6‰ for β‐alanine in RBT 04262 is in the range of reduced organic carbon previously measured in Martian meteorites (Steele et al. 2012). The presence of n‐ω‐amino acids may be due to a high temperature Fischer‐Tropsch‐type synthesis during igneous processing on Mars or impact ejection of the meteorites from Mars, but more experimental data are needed to support these hypotheses.